Redsharc: A Programming Model and On-Chip Network for Multi-Core Systems on a Programmable Chip. (15th November 2011) - Kritikos, William V.; Schmidt, Andrew G.; Sass, Ron; Anderson, Erik K.; French, Matthew
Abstract : The reconfigurable data-stream hardware software architecture (Redsharc) is a programming model and network-on-a-chip solution designed to scale to meet the performance needs of multi-core Systems on a programmable chip (MCSoPC). Redsharc uses an abstract API that allows programmers to develop systems of simultaneously executing kernels, in software and/or hardware, that communicate over a seamless interface. Redsharc incorporates two on-chip networks that directly implement the API to support high-performance systems with numerous hardware kernels. This paper documents the API, describes the common infrastructure, and quantifies the performance of a complete implementation. Furthermore, the overhead, in terms of resource utilization, is reported along with the ability to integrate hard and soft processor cores with purely hardware kernels being demonstrated.